Marketing estratégico en el posicionamiento de la marca Maganyl del Laboratorio Rocnarf en Guayaquil, año 2024 - Álava Yanez, Isaac Xavier (2024)
In the current context of the pharmaceutical market, there are several brands of gastro-protective digestive products or also known as drinkable products for the protection of the stomach. There are several brands on the market that are already positioned in the minds of consumers and cause a problem for new ones. brands to enter the competitive market. That is what happens with the Maganyl brand, it is a product that has been on the market for 4 years and offers benefits to its consumers, the problem is that consumers of this type of medicine do not easily recognize the brand so it is not well positioned. in the market. This research aims to analyze the strategic marketing in the positioning of the Maganyl brand of the Rocnarf laboratory in the city of Guayaquil, and as a proposal of this research is the strategic marketing that will help to promote the positioning and in turn generate more awareness of brand with consumers, with these achievements it will be possible to generate growth in the market and obtain future profits. Furthermore, in this research we were able to detail several analyzes that helped us collect data and know what the current state of the brand is like and what are the biggest symptoms that people have with super acidity and digestive problems.